Patient autonomy in an East-Asian cultural milieu: a critique of the individualism-collectivism model - Lim, Max Ying Hao (Journal of medical ethics, 2024)
The practice of medicine—and especially the patient-doctor relationship—has seen exceptional shifts in ethical standards of care over the past few years, which by and large originate in occidental countries and are then extrapolated worldwide. However, this phenomenon is blind to the fact that an ethical practice of medicine remains hugely dependent on prevailing cultural and societal expectations of the community in which it serves. One model aiming to conceptualise the dichotomous efforts for global standardisation of medical care against differing sociocultural expectations is the individualism-collectivism model, with the ‘West’ being seen as individualistic and the ‘East’ being seen as collectivistic. This has been used by many academics to explain differences in approach towards ethical practice on key concepts such as informed consent and patient autonomy. However, I argue that this characterisation is incomplete and lacks nuance into the complexities surrounding cross-cultural ethics in practice, and I propose an alternative model based on the ethics of clinical care in Hong Kong, China. Core ethical principles need not be culture-bound—indeed, their very existence mandates for them to be universal and non-derogable—but instead cultural alignment occurs in the particular implementation of these principles, insofar as they respect the general spirit of contemporary ethical standards.